Relationships between Attitude Towards Behaviour, Subjective Norm, Self-Efficacy and Entrepreneurial Intention Among the Technical Secondary Students in Malaysia - U.N, Saraih; M.H, Amlus; Hanie Abu Samah, Irza; Mutalib S, Abdul; Zuraini Zin Aris, Ain; A, Sharmini (International Journal of Engineering and Technology, 2018)
The present study investigated the relationships between the three factors of Theory of Planned Behavior (TPB) and entrepreneurial intention among students from the Technical Secondary School in Malaysia. This study utilized the survey (questionnaire) method. A total of 163 respondents which consisted of the Year 4 students from one of the Technical Secondary School in Northern Region of Malaysia were selected to participate in this study. The findings presented that students in this institution have a high level of entrepreneurial intention (mean=3.89). Also, results presented that subjective norm is the only factor that significantly related to entrepreneurial intention (Î²=.331, p=.000). Meanwhile, other factors such as attitude towards behavior (Î²=.064, p=.474) and self-efficacy (Î²=.070, p=.438) are not significantly related to entrepreneurial intention. Thus, it is found that only one factor of TPB which is subjective norm has a significant relationship with entrepreneurial intention among students in this Technical Secondary School. This study contributed some fruitful knowledge which can be suggested to all Technical Secondary Schools to improve the level of studentsâ€™ entrepreneurial intention, particularly in the Malaysian context. Implications of the results are discussed; and future research direction are briefly provided.Â Â